THE ROLE OF QUR’ ANIC RECITATIONS (QIRA’ AT) IN THE EXEGESIS OF THE HOLY QUR’ AN (The Journal of Interdisciplinary Human Studies, 2026)
This article presents a scholarly analysis of the role of Qur’ anic recitations(qira’ at) in the exegesis (tafsir) of the Holy Qur’ an. The science of Qur’ anic recitationsholds a distinctive position within the Islamic scholarly tradition and constitutesone of the fundamental sources for the discipline of Qur’ anic exegesis. This studyexamines how variant recitations expand the semantic scope of Qur’ anic verses, theirinfluence on jurisprudential rulings (fiqhi ahkam), and the methodological approachesemployed by classical exegetes (mufassirun) in utilizing these variant readings. Thefindings indicate that the majority of recitation variants are complementary in nature,collectively demonstrating the richness of Qur’ anic meanings. The study conducts acomparative analysis based on the works of al-Ṭabari, al-Zamakhshari, Ibn al-Jazari,and contemporary scholars.
Keywords: qira’ at; tafsir; Holy Qur’ an; mufassirun, variant recitations; jurisprudential; rulings